The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jso.25348
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the eighth edition AJCC staging system in early T1 to T2 oral squamous cell carcinoma

Abstract: Background To validate the newly proposed American Joint Committee on Cancer (AJCC) eighth edition staging in early T1 and T2 oral cavity cancers and its effect in predicting tumour control. Methods Retrospective analysis of treatment outcomes of 441 T1 to T2 oral squamous cell carcinoma (OSCC). Overall survival (OS), disease‐specific survival (DSS), and tumour control were calculated and compared between the AJCC 7 and 8 staging systems. Results The 5‐year OS was 78% and 61% for T1 and T2 tumours, respetively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…(112 patients, Japan) and Murthy et al . (441 only T1‐2 cancers, India) also showed that new staging system correctly reflects prognosis as compared to older one. One more study from the United States by Cramer et al .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…(112 patients, Japan) and Murthy et al . (441 only T1‐2 cancers, India) also showed that new staging system correctly reflects prognosis as compared to older one. One more study from the United States by Cramer et al .…”
Section: Discussionmentioning
confidence: 89%
“…With regard to their survival outcomes, we found that patients with upstaged disease had poor survival outcomes as compared to those with retained stage classification. In addition, CI, AIC and hazard modeling all favor new staging system for predicting outcomes, especially for TCs Japan) 12 and Murthy et al (441 only T1-2 cancers, India) 13 also showed that new staging system correctly reflects prognosis as compared to older one. One more study from the United States by Cramer et al concluded marginally improved prognostic ability for AJCC8 (0.699-0.704).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, 20 studies were eligible as they evaluated the prognostic performance of AJCC 8 in OSCC (Figure 1). Of these, seven studies were from Asia, [18][19][20][21][22][23][24] four were from Australia, 12,[25][26][27] four from Europe, [28][29][30][31] four from North America, 14,[32][33][34] and one from South America. 35 In addition, a Brazilian cohort was analyzed in one of the published studies combined with a Finnish cohort.…”
Section: Search Resultsmentioning
confidence: 99%
“…28 Most studies included different subsites of OSCC, and only four studies included oral tongue SCC without any other subsite. 18,28,29,33 Overlapping studies were from Australia 12,25,26 and India 20,21 ; and they were not included together in the present meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation